(untitled) (مجلة إحالات, 2026)
This article explores how literature, particularly poetry, has turned its focus towards reviving human values duringthe pandemics. It has not been isolated from their effects and has vividly mirrored the fundamental shifts that accompany them, thereby translating the collective concerns. The article highlights one of the contemporary poets, Algerian Abd al-Malik Boumanghel, whose verses resonated during the time of the coronavirus. In his poem "The Sorrow of Minarets," he mourned the emptiness of mosques and the loss of their congregations. Through this, he created a creative space, blending linguistic aesthetics with the sincerity of experience, conveying poignant meanings and comprehensive descriptions that did not diminish its significance. While COVID-19 restricted the details of life and paralyzed it, poetry provided a window of hope.